N-Acetylcysteine Protects the Stem Cells of the Apical Papilla - Countryman, Kyle; Chen, Yen-Wei; Johnson, James D.; Paranjpe, Avina (Frontiers in Dental Medicine, 2022)
Objective Previous research has demonstrated that stem cells of the apical papilla (SCAP) have a lower differentiation potential and are less resistant to cell death as compared to other stem cells. N-acetyl cysteine (NAC) prevents apoptosis of the dental pulp stem cells (DPSCs) by inducing differentiation of these cells. The use of NAC with SCAP could possibly, enhance their differentiation and resistance to cytotoxicity. Hence, the aim of this study was to determine if NAC could prevent apoptosis of SCAP by promoting proliferation and differentiation of these cells thereby contributing to the success of Regenerative endodontic procedures (REPs). Methods Human SCAP were cultured with and without 2-hydroxyethyl methacrylate (HEMA), 20 mM NAC and Dexamethasone (Dex). Proliferation rates were analyzed at days 4 and 7. Flow cytometric analysis was used to analyze the levels of cell death. Differentiation of the cells was analyzed using Real-time PCR and an ALP assay. Data were analyzed using ANOVA with a post-hoc Tukey test. Results The NAC-treated cells had similar cell viability compared with the controls. The cells treated with NAC + HEMA had significantly higher rates of proliferation as compared to the HEMA only treated groups and displayed more cell viability when these groups were compared with flow cytometric analysis. Real-time PCR and the ALP assay demonstrated that the NAC group upregulated ALP, RUNX-2, and DSPP genes. Conclusion The data demonstrated that NAC protects the SCAP from apoptosis and enhances the proliferation and differentiation potential of these cells suggesting that NAC could be used effectively during REPs.